Relationship between periodontal disease and obstructive sleep apnea in adults: A systematic review - Edoardo Bianchi; Marzia Segù; Andrea Toffoli; Geremia Razzini; Guido Maria Macaluso; Edoardo Manfredi (Wolters Kluwer Medknow Publications, 2024)
The purpose of this systematic review was to evaluate whether there are scientific evidence regarding the association between periodontitis and obstructive sleep apnea (OSA) in adults. An electronic search was performed on MEDLINE/PubMed for prospective and retrospective longitudinal studies, cohort studies, and case-control studies conducted in human adults affected by both OSA and periodontitis. Two reviewers extracted the data using a custom Excel spreadsheet. A methodological assessment of the quality of the studies was performed using the Newcastle-Ottawa Scale. Fourteen studies were included. All studies evaluated the association between periodontitis and OSA. None of the studies evaluated the cause-effect relationship. Eleven studies found a significant positive relationship between periodontitis and OSA, whereas three found no statistically significant association. Several study limitations were observed, such as lack of standardization of study groups, diagnosis of periodontitis and OSA, and differences in study design. Evidence of a plausible association between periodontitis and OSA was found. The possible relationship could be explained by systemic inflammation, oral breathing, and the comorbid relationship attributable to common risk factors. Observational and randomized controlled studies are needed to clarify the mechanism of interaction between the two conditions.